Theileria parva antigens recognized by CD8+ T cells show varying degrees of diversity in buffalo-derived infected cell lines - Sitt, Tatjana; Pelle, Roger; Chepkwony, M.C.; Morrison, W. Ivan; Toye, Philip G. (Cambridge University Press, 2018)
The extent of sequence diversity among the genes encoding 10 antigens (Tp1–10) known to be recognized by CD8+T lymphocytes from cattle immune toTheileria parvawas analysed. The sequences were derived from parasites in 23 buffalo-derived cell lines, three cattle-derived isolates and one cloned cell line obtained from a buffalo-derived stabilate. The results revealed substantial variation among the antigens through sequence diversity. The greatest nucleotide and amino acid diversity were observed in Tp1, Tp2 and Tp9. Tp5 and Tp7 showed the least amount of allelic diversity, and Tp5, Tp6 and Tp7 had the lowest levels of protein diversity. Tp6 was the most conserved protein; only a single non-synonymous substitution was found in all obtained sequences. The ratio of non-synonymous: synonymous substitutions varied from 0.84 (Tp1) to 0.04 (Tp6). Apart from Tp2 and Tp9, we observed no variation in the other defined CD8+ T cell epitopes (Tp4, 5, 7 and 8), indicating that epitope variation is not a universal feature ofT. parvaantigens. In addition to providing markers that can be used to examine the diversity inT. parvapopulations, the results highlight the potential for using conserved antigens to develop vaccines that provide broad protection againstT. parva.